The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/stem.1469
|View full text |Cite
|
Sign up to set email alerts
|

Functional endothelial progenitor cells selectively recruit neurovascular protective monocyte-derived F4/80+/Ly6c+ macrophages in a mouse model of retinal degeneration

Abstract: Retinitis pigmentosa is a group of inherited eye disorders that result in profound vision loss with characteristic retinal neuronal degeneration and vasculature attenuation. In a mouse model of retinitis pigmentosa, endothelial progenitor cells (EPC) from bone marrow rescued the vasculature and photoreceptors. However, the mechanisms and cell types underlying these protective effects were uncertain. We divided EPC, which contribute to angiogenesis, into two subpopulations based on their aldehyde dehydrogenase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 53 publications
(86 reference statements)
0
26
0
Order By: Relevance
“…Interestingly, the Ly6C + (GR1 + )CCR2 + monocytes/macrophage subset that is depleted by the anti-CCR2 antibody is the subset known to preferably infiltrate into tissues and to have increased expression levels of anti-inflammatory cytokines like IL-10 and transforming growth factor beta. 9,13,39 Therefore, we suggest that the more pronounced effect of anti-CCR2 is due to the depletion of the anti-inflammatory effect–producing Ly6C + CCR2 + subset of monocytes/macrophages as opposed to the more general depletion of all monocytes/macrophages when using clodronate liposomes. An alternative possibility would be that the depletion with clodronate liposomes is less efficient or that repopulation is faster after depletion with clodronate liposomes than after depletion with anti-CCR2.…”
Section: Discussionmentioning
confidence: 84%
“…Interestingly, the Ly6C + (GR1 + )CCR2 + monocytes/macrophage subset that is depleted by the anti-CCR2 antibody is the subset known to preferably infiltrate into tissues and to have increased expression levels of anti-inflammatory cytokines like IL-10 and transforming growth factor beta. 9,13,39 Therefore, we suggest that the more pronounced effect of anti-CCR2 is due to the depletion of the anti-inflammatory effect–producing Ly6C + CCR2 + subset of monocytes/macrophages as opposed to the more general depletion of all monocytes/macrophages when using clodronate liposomes. An alternative possibility would be that the depletion with clodronate liposomes is less efficient or that repopulation is faster after depletion with clodronate liposomes than after depletion with anti-CCR2.…”
Section: Discussionmentioning
confidence: 84%
“…For example, inflammatory cytokines are increasingly recognized as playing an important role in tissue regeneration (45). One group demonstrated that EPC-derived CCL2 recruited neuroprotective microglia in an acute retinal degeneration model (46). Interaction between HA and CD44 has known to induce chemokine expression, which recruits and activates leukocytes (47).…”
Section: Discussionmentioning
confidence: 99%
“…Results were presented as percent positive cells over total cells per 0.1 mm 2 . Five randomly chosen independent fields were used for quantification according to previously described methods (18,27).…”
Section: Spontaneous Voluntary Activitymentioning
confidence: 99%